1997
DOI: 10.1021/ef970007a
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Macromolecular Structure of a Type I Kerogen during Maturation

Abstract: The solvent swelling of a maturation series consisting of 5 Type I kerogens from the Uinta basin has been studied. The swelling of the kerogens in 10 solvents has been used to determine the solubility parameter (δ) of the samples. It is 9.5-10.0 (cal/cm 3 ) 1/2 . The same data have been used to calculate the number average molecular weights between cross-links (reciprocal of the cross-link density) for the samples. The cross-linking increases during early maturation, and sharply above 80% maturation, but remai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 10 publications
1
34
0
Order By: Relevance
“…50 The kerogen molecules typically possess on average 2-5-ring PAH units that are highly substituted, [51][52][53] and during thermal maturation, kerogen is transformed from a macromolecule characterized by a significant aliphatic component to one containing shorter chains dominated by more condensed PAH structures. [54][55][56][57] From their basic geochemical origin, it can be concluded that asphaltenes should contain multiple PAH units inside their molecules, which is consistent with the PAH distribution produced from their pyrolysis.…”
mentioning
confidence: 72%
“…50 The kerogen molecules typically possess on average 2-5-ring PAH units that are highly substituted, [51][52][53] and during thermal maturation, kerogen is transformed from a macromolecule characterized by a significant aliphatic component to one containing shorter chains dominated by more condensed PAH structures. [54][55][56][57] From their basic geochemical origin, it can be concluded that asphaltenes should contain multiple PAH units inside their molecules, which is consistent with the PAH distribution produced from their pyrolysis.…”
mentioning
confidence: 72%
“…Similar values for retention of EGME before and after OM removal from sedimentary samples were observed by Tiller and Smith (1990) and Kennedy et al (2002), and so suggested that OM does not react with EGME. In contrast, Larsen and Li (1997) and Larsen et al (2002) presented evidence that Type I and Type II kerogens of different degrees of maturation react chemically with organic molecules and swell in polar organic liquids, although those liquids seem to react differently depending on the various major constituents of OM (Cornelissen et al, 2005 and references therein). The similarity of kerogen (Larsen and Li, 1997;Larsen et al, 2002) and soil humic acid (Chiou et al, 1988) reactions with various organic liquids suggests that sedimentary OM may retain EGME via the mechanism demonstrated by Chiou et al (1993) for soil OM.…”
Section: Egme Retention and Cec Measurement In Organic-rich Rocksmentioning
confidence: 98%
“…There have been extensive experiments on the adsorption of gases in shales and kerogens. However, experiments on gas sorption-induced shale swelling are limited. , The extensive experiments performed on liquid sorption-induced kerogen swelling have mainly been conducted at room conditions. Larsen et al have measured swelling of different types of kerogen; the measured swelling is in the range of 10 to 25% in normal pentane ( n -C 5 H 12 ) and normal heptane ( n -C 7 H 16 ). Kelemen et al report that Type II kerogen can swell 23 and 21% in normal decane ( n -C 10 H 22 ) and normal hexadecane ( n -C 16 H 34 ), respectively.…”
Section: Introductionmentioning
confidence: 99%